Indigenous Governance Systems and Democracy in Ethiopia: Yejoka Qicha System of the Gurage People - Bitew, Birhanu; Sewenet, Asabu; Fentahun, Getachew (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
Indigenous governance systems within the Eastern African nation of Ethiopia are often dismissed by Western political elites as undemocratic. We assessed the nature of and level of democracy in Indigenous governance systems in Ethiopia by focusing on the Yejoka Qicha of the Gurage people. We found that, while the Yejoka Qicha system includes democratic elements that can support national efforts to consolidate democracy, it also marginalizes some groups, such as women, from political and economic benefits. As such, we recommend the implementation of policies that eliminate the oppressive aspects of the Yejoka Qicha system, while also recognizing the role that these Indigenous governance systems can have in promoting democracy within Ethiopia.